2016
DOI: 10.1016/j.biortech.2016.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Chlorella pyrenoidosa in outdoor open raceway pond using domestic wastewater as medium in arid desert region

Abstract: Chlorella pyrenoidosa was cultivated in secondary wastewater effluent to assess its nutrient removal capabilities. Wastewaters were obtained from a wastewater treatment plant located in Ouargla, Algeria. The experiments were conducted in winter under natural sunlight in an outdoor open raceway pond situated in the desert area. The highest biomass of the microalgae was found to be 1.71±0.04g/L. Temperatures ranged between 18 and 31°C. The average annual insolation was no less than 3500h with an annual solar irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(21 citation statements)
references
References 15 publications
1
18
1
1
Order By: Relevance
“…In other studies, removal rate of total nitrogen was observed between 61.1% -91.8% by Chlorella sp. grown in municipal wastewater [47] [48] [49] whereas 87.9% removal was recorded in this study. It was observed that 98.4% of total phosphorous was removed which is higher than removal rate reported in previous studies [46] [50] [51].…”
Section: Resultsmentioning
confidence: 68%
“…In other studies, removal rate of total nitrogen was observed between 61.1% -91.8% by Chlorella sp. grown in municipal wastewater [47] [48] [49] whereas 87.9% removal was recorded in this study. It was observed that 98.4% of total phosphorous was removed which is higher than removal rate reported in previous studies [46] [50] [51].…”
Section: Resultsmentioning
confidence: 68%
“…The United States Environmental Protection Agency designated medium (EPA medium, containing 96 mg/L NaHCO 3 , 60 mg/L CaSO 4 , 60 mg/L MgSO 4 , and 4 mg/L KCl, pH 7.5) was used for culture. The single‐cell green alga Chlorella pyrenoidosa was cultured to the exponential growth phase in the BG‐11 medium (Dahmani, Zerrouki, Ramanna, Rawat, & Bux, 2016), harvested by centrifugation at 4,000 g for 15 min, and stored at 4°C for feeding rotifers (Guo, Snell, & Yang, 2011). After acclimation for 3 months, rotifers were used for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…A stock solution of 250 mg/L nTiO 2 was prepared by dispersing the nanoparticles in ultrapure water (Direct-Pure adept, RephiLe Bioscience, China) and sonication in a water-bath ultrasonic cleaner (JP-060ST, Skymen, China) for 30 min (Wang et al, 2016). | 231 phase in the BG-11 medium (Dahmani, Zerrouki, Ramanna, Rawat, & Bux, 2016), harvested by centrifugation at 4,000 g for 15 min, and stored at 4°C for feeding rotifers (Guo, Snell, & Yang, 2011). After acclimation for 3 months, rotifers were used for experiments.…”
Section: Materials and Test Organismsmentioning
confidence: 99%
“…Open air systems have a low energy cost for cultivation as they utilize solar energy. However, there are limitations to controlling operation conditions such as light intensity or temperature, and thus optimal periods for algal cultivation and the selective cultivation of specific algal groups are limited [15][16][17][18]. Thus, closed systems are preferred to optimize algal cultivation conditions for biofuel production and nutrient removal in wastewater treatment plants as the operational parameters, such as characteristics and intensities of light, are controllable [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%